Intensive Blood Pressure Control and Diabetes Mellitus Incidence for Patients with Impaired Fasting Glucose: A Secondary Analysis of SPRINT - Beiru Lin; Xiaochuan Liu; Sichen Yao; Zhigang Pan (International Journal of Hypertension)
Background. Previous studies indicated that intensive blood pressure (BP) control (systolic BP < 120 mm·Hg) compared with standard BP control (<140 mm·Hg) was associated with an increased risk of type 2 diabetes (T2D) and impaired fasting glucose (IFG) among hypertensive patients with normoglycemia. However, the impact of intensive BP control on the incidence of T2D for those with IFG is still unknown. Methods. This was a secondary analysis of the SPRINT (Systolic Blood Pressure Intervention Trial) of the study. We included participants with IFG at randomization, which was defined as fasting blood glucose (FBG) between 100 and 125 mg/dL. The primary outcome was incident T2D, defined as events of reaching FBG ≥ 126 mg/dL, participant self-report T2D at annual examination, or a record of hypoglycemic medications at follow-up. The secondary outcome was incident IFG reversion (IFGR), defined as the time to first FBG back to normoglycemia (<100 mg/dl) among participants without incident T2D. Cox proportional hazards models were used to compare the cumulative incidence of outcomes between the two BP control groups. Hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated. Results. A total of 3310 participants were included in our primary outcome analysis (median age 67 years, 29% female). There were 293 participants who developed T2D among the intensive BP control group and 256 participants who developed T2D among the standard BP control group, resulting in 56.87 (50.36–63.39) versus 49.33 (43.29–55.37) events per 1000 person-years of treatment (HR 1.18 [95% CI, 1.00–1.40], P=0.052). After excluding 549 participants who developed T2D, 2761 participants were included in our secondary outcome analysis with 559 participants who developed IFGR among the intensive BP control group and 632 participants who developed IFGR among the standard BP control group, resulting in 141.20 (129.50–152.91) versus 158.20 (145.86,170.53) events per 1000 person-years of treatment (HR 0.9 [95% CI, 0.8–1.01], P=0.067). Conclusions. Our study found that in comparison to the standard BP control for hypertensive patients with IFG, intensive BP control was associated with a small increased risk of new-onset T2D, though it did not reach statistical significance. This kind of impact should be considered when implementing the strategy, especially for those with high risks of developing T2D. This trial is registered with NCT01206062.